EVALUASI KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN MUSI BANYUASIN MELALUI PENDEKATAN VALUE FOR MONEY - Akhmad Irfansyah; Jumania Septariani (Institut Rahmaniyah Sekayu, 2021)
The purpose of this study was to determine the regional financial performance of the Regional Government of Musi Banyuasin Regency in terms of the value for money approach. Types and sources of data used by the author in this study are secondary data. The results of the study stated that the Government of Musi Banyuasin Regency applied Value for Money as a concept of measuring its performance. With the concept of Value for Money, the government measures organizational performance more comprehensively, so that the government improves its performance in the future. The economic ratio of the Musi Banyuasin Regency Government showed the performance of the regional government in 2015 to 2019 with an average ratio of 87.08%, indicating that this ratio is of economic value. The performance efficiency ratio of the Musi Banyuasin Regency Government was quite good. In 2016 to 2019 was efficient, although in 2015 it showed an inefficient ratio. The effectiveness ratio in the Musi Banyuasin Regency Government for the period 2015 to 2019 with an average ratio value of 94.78%, the effectiveness ratio of <100% indicating that the performance of the Musi Banyuasin Regency government in that year was considered ineffective.